Part of the Policing System in Criminal Justice System; Pieces of evidence from Punjab, Pakistan - Nazir, Sadaqat ali (Journal of Peace, Development and Communication, 2022)
Understanding criminal justice procedure in depth is imperative for developing a peaceful and nonviolent society. The police department is a crucial component of any country’s criminal justice system. The aim of current research was to examine Pakistan’s criminal justice system, with a special focus on the Punjab police department as this department is the core part of this CJS (Criminal Justice System) hierarchy. In this study, the researcher employed the quantitative research design, and 104 out of 210 convicted prisoners were interviewed from the Faisalabad District Jail with the help of a well-structured questionnaire. It can be concluded that the policing system of Pakistan has developed through time and is continuing to do so in the modern world, including Pakistan; yet, the intricate workings of the system can be simplified enough for the average person to comprehend them, taking into account the changing interests and challenges of different time and spaces.